Identification of Perceived Self-Efficacy to Predict Student’s Awareness in Career Readiness: Array - Alfaiz Alfaiz; Hendra Hidayat; Hengki Yandri; Aprilia Tina Lidya Sari; Fendahapsari Singgih Sendayu; Septya Suarja; Arjoni Arjoni (Islamic Guidance and Counseling Journal, 2021)
Research found that self-efficacy has an important role in the development of students’ career cognitive skills. Besides, there still needs further research in self-efficacy, particularly in career readiness. The authors conduct this continuing study is to determine the effect of understanding perceived self-efficacy on student’s awareness in career readiness (mastery experience, vicarious experience, social persuasion, and emotional arousal). Data collected using a self-report of the Self-Efficacy Scale in Career Readiness (SESCR), semi-structured interview, and observation of student’s behavior between both participants with the high and low level of self-efficacy. In the current study, 100 students involved based on their convenience. Results showed that 66% of participants have a high mastery experience, 69% with high vicarious experience, 76% have a high percentage in social persuasion, and 70% have a high level of emotional arousal to understanding their career readiness. The results also showed perceived self-efficacy predicts student’s awareness of career readiness based on gender.